PORTRAIT OF NOTHINGNESS THROUGH THE CHARACTERIZATION OF GREGOR IN KAFKA'S THE METAMORPHOSIS - Efifatus Solihah; Ari Setyorini; Pramudhana Ihsan (Tell : Teaching of English Language and Literature Journal, 2017)
The researcher used Franz Kafka‟s The Metamorphosis because the story in that novel contained the concept ofexistentialism, namely nothingness which was experienced by the main character, Gregor. The objectives of thisresearch were for describing the characterization of Gregor in that novel, and analyzing Gregor‟s representationof nothingness in that novel. In this research, the researcher used the descriptive qualitative to analyze the datawhich was depend on the statements of the problem. On the other hands, the researcher also used two dataresources; they were library and internet resources. From this research, the researcher found Gregor‟scharacterization which told about the way of understanding about his characteristics. Those were negativecharacteristics which were represented through direct and indirect method. Moreover, the researcher foundGregor‟s nothingness or non-being because he had negative characteristics in himself. As long as heexperienced that position, he was incapable to conduct the job. Instead, he refused his existence, and hepreferred to live by locking himself in his room, exactly under the mattress. Thus, his parents and his sistercould not meet and find him anytime to make him free as human being